Google Meet for English Speaking Activities: Students' Views on Its Effectiveness - Marzulina, Lenny; Erlina, Dian; Herizal, Herizal; Holandyah, Muhamad; Harto, Kasinyo; Pagarayu, Mifza (Universitas Jambi, Indonesia, 2023)
The current technological development has made online learning an alternative for teachers and students to carry out instruction. One of the learning applications that is often used is Google Meet. This research was conducted to find out the students' perceptions toward the use of Google Meet for speaking activities at a private Islamic Senior High School (Madrasah Aliyah) in Palembang, South Sumatera. The study employed a qualitative research design, and the participants were twelve 11th-grade students from the science and social studies departments. Data were collected through interviews, which were recorded and transcribed. The findings of this research revealed that learning speaking through the Google Meet application was perceived negatively by the students, indicating its ineffectiveness in facilitating their speaking activities. Several views were identified: (1) using Google Meet decreased student engagement in speaking activities, (2) it did not create an enthusiastic learning atmosphere for speaking, (3) it reduced students' attention to learning speaking, and (4) it was unhelpful in improving the students' speaking skills. These implied that the use of Google Meet application was ineffective for English speaking activities. However, it could be used as a supplementary online English teaching media.